THE IMPACT OF SUPPORTING INDUSTRIES ON ELECTRONIC INDUSTRY: THE CASE OF VIETNAM ENTERPRISE SURVEY - Tran Viet Thao, Vu Thi Thanh Huyen, Le Mai Trang, Bui Lan Phuong, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This paper used the Vietnamese enterprise survey and GMM method to estimate the impact of supporting industries on eclectronic industry. The results show that, supporting industry development is one of the important factors affecting the development and promoting the competitiveness of the Vietnamese electronics industry. The findings of study suggest that, it is necessary to promote the development of supporting industries through the formulation and completion of policies on science and technology; It is also necessary to have policies to attract experts from countries with development support industries to Vietnam to advise, train and improve the level of science and technology and the quality of human resources.